COUNSELING GUIDANCE IN ELEMENTARY SCHOOLTHE PANDEMIC: CASE STUDY OF DURING CENDIKIA COUNSELING LITERACY (CCL) AT SD IT CENDEKIA - Wina Mustikaati; Agus Muharam; Hisny Fajrussalam; Aprilia Sanny; Fitri Yani (AT-TAJDID, 2021)
Literacy is an important thing in the world of education, the importance of literacy requires guidance and counseling. Under normal conditions, the counseling service activities, both educational cinema or CCL, are carried out classically or in groups. However, with the current condition of the Covid pandemic, of course these service activities must continue. To overcome this, the use of CCL is one of the literate counseling techniques to continue to provide counseling services to students. CCL is a Literacy Counseling Scholar is a counseling activity that uses reading media to teach children about literacy. These various literacys will intervene in the behavior of students. This research uses a case study method with low grade objects, in order to analyze and reveal the extent to which CCL can provide life skills, independence and a culture of literacy. It is hoped that by obtaining this study in the future it can create solution ideas as an effort to improve the literacy skills of elementary school studentsKeywords: Guidance Counseling, Counseling Literacy, Cendikia Counseling Literacy